Penerapan Azaz Desentralisasi Pada Penyelenggaraan Pelayanan Publik Di Kota Manado - Areros, William Agustinus (JURNAL ILMIAH SOCIETY, 2015)
Government decentralization implementation is realized by granting autonomy to the region aims to enable the region to improve the effectiveness and efficiency in governance in the context of public service and implementation of development. Reality shows government officials have not been able to provide a quality service to the public in accordance community expectations. Through the use of qualitative analysis found that government officials have not been able to provide a quality service to the public in accordance community expectations as a result of the delegation of authority that occurs not surrender the rights of superiors to subordinates, but the delivery of the right of officials to officials. decentralization in improving the quality of public services has the meaning that the quality of public services that are run by the government at a working level dependent or co-determined by the transfer of part of the authorities in the context of decentralization of administration utilized efficiently and effectively Keywords: Decentralization, Public Services, Local Government